2017
DOI: 10.1007/s00066-017-1194-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk-adapted robotic stereotactic body radiation therapy for inoperable early-stage non-small-cell lung cancer

Abstract: CyberKnife® lung SBRT which allows for real-time tumor tracking and risk-adapted fractionation achieves satisfactory local control and low toxicity rates in inoperable early-stage primary lung cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
24
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 33 publications
7
24
3
1
Order By: Relevance
“…The development of modern radiation technologies ensures that these elderly, frail patients can be treated safely. [30][31][32] The results of the current study stand in contrast to a SEER analysis by Shaikh et al, which shows that CSS and on univariate analysis -OS are better in patients without histologically confirmed disease. 25 More than 7000 patients were included, 90% of which had pathology.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…The development of modern radiation technologies ensures that these elderly, frail patients can be treated safely. [30][31][32] The results of the current study stand in contrast to a SEER analysis by Shaikh et al, which shows that CSS and on univariate analysis -OS are better in patients without histologically confirmed disease. 25 More than 7000 patients were included, 90% of which had pathology.…”
Section: Discussioncontrasting
confidence: 91%
“…Simultaneously, the adoption of screening programs for lung cancer will lead to the detection of numerous small lesions in high‐risk populations in potentially limited general condition, which may preclude invasive diagnostic procedures. The development of modern radiation technologies ensures that these elderly, frail patients can be treated safely …”
Section: Discussionmentioning
confidence: 99%
“…First of all, our LC rates are well in line with results from previous series of lung SBRT and specifically CyberKnife SBRT ( 5 , 7 9 , 13 , 21 24 , 51 54 ). We found that the PTV prescription BED 10 was a significant factor for LC which is in agreement with our previous and with large multi-institutional studies ( 5 , 7 9 , 13 , 38 , 39 , 55 , 56 ).…”
Section: Discussionsupporting
confidence: 91%
“…Two studies assessed the toxicity and efficacy of IGSBR in a high-risk population of patients with early stage but medically inoperable lung cancer (IOLC). [ 18 , 19 ] One concluded that patients with nonsmall cell IOLC received SBRT had a survival rate of 55.8% at 3 years. [ 18 ] In addition, it also had high rates of local tumor control, and moderate treatment-related morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the other one demonstrated that IGSBR allows for real-time tumor tracking and also the risk-adapted fractionation achieves satisfactory local control and low toxicity rates in patients with IOLC at early stage. [ 19 ] The other study compared the effects between central and peripheral stage I lung cancer using IGSBR by helical tomotherapy. [ 20 ] It is found that helical IGSBR for the treatment of central stage I lung cancer is safe and effective, when it is compared with the patients in peripheral stage I lung cancer.…”
Section: Discussionmentioning
confidence: 99%